(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
Abstract: Objectives: Assessment of certain cell mediated parameters during different clinical stages of pulmonary tuberculosis (PTB). Materials and method: Two hundred and ten patients with different clinical stages of PTB and 105 healthy individuals were enrolled in this study. Both study groups were submitted to; tuberculin skin test (TST) to assess the delayed type hypersensitivity resection (DTH); skin sensitization to 1-chloro 2,4-dinitrobenzene (DNCB) to determine the non-specific immune response (NIR); assessment of peripheral phagocytic activity (PPA) by nitro-blue tetrazolium (NBT) reduction test. Additionally, correlation of these immune parameters with peripheral total CD4+ and CD8+ T lymphocyte counts were also sought.